Evaluation of Sialometric Analysis of Patients Suffering from Depressive Disorders - Milton, Annette B.; Bhambal, A.; Nair, P. (Kathmandu University Medical Journal, 2017)
Background Depressive disorders, worldwide, may rank second by the year 2020. In India; about 10 million people suffer from depressive disorders, the prevalence rate being recorded as 31.2 for every 1000 individuals. A significant impairment of all personal hygiene may occur due a depressive episode which in turn may result in altered salivary flow. Objective The present study was a hospital- based clinical cross-sectional study which was conducted in Bhopal, the heart of Madhya Pradesh, India. It was done to assess the relationship of bring about a comparison of sialometric alterations between normal and subjects with depressive disorders. Method The survey period extended over a period of one year and two months, from May 2009 to July 2010. It was conducted in Bhopal, Madhya Pradesh, Central India. A sample size of 150 individuals, 50 of each group, was taken in the study. Whole salivary flow rates were determined by gravimetric method (i.e. in millilitres per minute). The Tenovuo criterion was used, to which numerical scores (SFI) were attributed. Result Results showed that the unstimulated salivary flow rates between patients of Group I and Group III (p< 0.0001) and between Group II and Group III (p < 0.0001) were statistically significant. The study also showed statistically significant relation between subjective and objective oral dryness (chi 2= 55.789, df= 6 and p< 0.0001). Conclusion It was observed that subjective sensation of dry mouth may exist even in the presence of normal salivary flow rates. This might be acknowledged as a psychophysiological expression of depression and may not necessarily reflect actual salivary gland function. The lack of secreted mucins rather than the quantity of saliva may play a role in the genesis of xerostomia.